Effect of taxpayer awareness, tax knowledge, quality of tax service, and tax sanctions on compliance with property tax - Eka Safitri, Yulia (Publication Division of International Ecsis Association, 2022)
This study aims to determine the effect of taxpayer awareness, tax knowledge, quality of tax services, and tax sanctions on land and building tax compliance. The sampling technique used is simple random sampling. The final sample of observations was 96 respondents. The analytical method used is multiple linear regression analysis with the SPSS 25 application program. The results of this study indicate that awareness of taxpayers, tax knowledge, and quality of tax services do not affect the compliance of land and building taxpayers. While tax sanctions affect the compliance of land and building taxpayers.